Malnutrition In The Outpatient Department of Child Nutrition Dr. Pirngadi Hospital Medan ( 1976 - 1979) - Nasril Nazir; Sjarikat Tarigan; Helena Siregar; Djaman Purba; Nangsang Sitepu (Indonesian Pediatric Society, 1984)
A 4 years retrospective study was made on malnourished children attending the OPD of the Sub Department of Child Nutrition, Dr. Pirngadi Hospital during the period of 1976 - 1979. In this study 635 out of 720 malnourished children were under 3 years old. Gain in body weight was only seen in 23,7% of the children. Most of them (49, 7% came only once. More effort such as child food demonstration, health and nutrition education is needed to motivate the parents to bring their malnourished children for consultation.